Complex Conductivity of Graphitic Schists and Sandstones. Issue 8 (22nd August 2019) - Abdulsamad, F.; Revil, A.; Ghorbani, A.; Toy, V.; Kirilova, M.; Coperey, A.; Duvillard, P.A.; Ménard, G.; Ravanel, L.
Abstract: Spectral induced polarization spectra were carried out on three graphitic schists and two graphitic sandstones. The microstructural arrangement of graphite of two graphitic schists was studied with thin sections using transmitted and reflected light optical and electron microscopic methods. Chemical maps of selected areas confirm the presence of carbon. The complex conductivity spectra were measured in the frequency range 10 mHz to 45 kHz and in the temperature range +20 °C down to −15 °C. The measured spectra are fitted with a double Cole‐Cole complex conductivity model with one component associated with the polarization of graphite and the second component associated with the Maxwell‐Wagner polarization. The Cole‐Cole exponent and the chargeability are observed to be almost independent of temperature including in freezing conditions. The conductivity and relaxation time are dependent on the temperature in a predictable way. As long as the temperature decreases, the electrical conductivity decreases and the relaxation time increases. A finite element model is able to reproduce the observed results. In this model, we consider an intragrain polarization mechanism for the graphite and a change of the conductivity of the background material modeled with an exponential freezing curve. One of the core sample (a black schist), very rich in graphite, appears to be characterized by a very high conductivity (approximately 30 S/m). Two induced polarization profiles are discussed in the area of Thorens. The model is applied to the chargeability data to map the volumetric content of graphite. Key Points: Graphite‐bearing rocks exhibit anomalous electrical properties New experimental data are shown to characterize the electrical properties of these rocks A model is developed to explain the new observations